Predictive outcomes of revision total hip replacement--a consecutive series of 1176 patients with a minimum 10-year follow-up. - Philpott, A; Weston-Simons, J; Grammatopoulos, G; Bejon, P; Gill, H; McLardy-Smith, P; Gundle, R; Murray, D; Pandit, H (2014)
The burden of revision total hip replacement (THR) surgery is increasing. With an increasing life expectancy and younger age of primary surgery this trend is set to continue. There are few data on the long-term outcome of revision THR. This retrospective study of 1176 consecutive revision THRs with a minimum 10-year follow-up from a University Teaching Hospital was undertaken to review implant survival and patient reported outcomes. Mean follow-up was 11 years with implant survival at 10 years of 82% (CI: 80-85). Implant survival varied between 58% (unexplained pain) to 84% (aseptic loosening) depending on the indication for revision surgery. Positive predictors of survival were age greater than 70 at the time of surgery (p=0.011), revision for aseptic loosening (p<0.01) and revision of both components or just the acetabular component (p<0.01). At the last review, mean Oxford Hip Score (OHS) was 34 (SD: 11.3) and 92% of the living patients with unrevised hips were satisfied with the outcome of revision surgery. This long term study has demonstrated that positive predictors of survival and outcome of revision THR surgery are age greater than 70 years, revision for aseptic loosening and component revision. This should aid surgeons in their counselling of patients prior to surgery.